Exploratory and confirmatory factor validation and psychometric properties of the HR roles for HR managers in Malaysia / Yusliza Mohd. Yusoff and Hasliza Abdul Halim - Mohd. Yusoff, Yusliza; Abdul Halim, Hasliza (Research Management Institute (RMI), 2010)
The effectiveness ofthe Human Role Assessment Survey Questionnaire, HRASQ. (Conner and Ulrich. 1996) was investigated with a sample of 108 Human Resource (HR) managers. The exploratory and confirmatory factor analyses showed that the 3-subscale structure of the HRASQ was valid. In addition, the results verified that the HRASQ had high internal reliability. These results indicated that the HRASQ and its subscales can be used in research related to role ofthe HR in Malaysia.